LEGAL REGIME OF SOME ATYPICAL COPYRIGHT OBJECTS: PROBLEMATIC ISSUES - Diduk, Alla; Lytvyn, Stepan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to consider problematic issues regarding the legal regime of some atypical copyright objects. For this purpose, the concepts of "atypical objects of civil law", "atypical objects of intellectual property law" and "atypical objects of copyright" were analyzed. As a result of the analysis, the peculiarities of the legal protection of atypical copyright objects and the problems of their protection in court were considered. The methodological basis of the research is general scientific and special methods of scientific knowledge. The use of these methods made it possible to analyze the legal regime of some atypical copyright objects and describe the problems of their legal protection. Results: the atypicality of copyright objects requires not only meaningful certainty, but also a formal and logical one, designed for stable practical application. Despite the presence of separate studies on this issue, atypicality requires analysis in the context of copyright objects, and the contradiction and ambiguity of the current legislation and the practice of its application affects the understanding of a certain object and its legal regime. Discussion: with the development of information technologies, their spread to all spheres of people’s lives, without exception, there is a modification of already existing traditional objects of copyright, as well as the appearance of new atypical objects of copyright. Therefore, the specified objects require a detailed study, and the identification of their features will allow the introduction of norms into the current legislation for their effective legal protection and protection of authors’ rights.